Probing baryogenesis with neutron-antineutron oscillations - Kåre Fridell (SpringerOpen, 2021)
Abstract In the near future, the Deep Underground Neutrino Experiment and the European Spallation Source aim to reach unprecedented sensitivity in the search for neutron-antineutron (n- n ¯ $$ \overline{n} $$ ) oscillations, whose observation would directly imply |∆B| = 2 violation and hence might hint towards a close link to the mechanism behind the observed baryon asymmetry of the Universe. In this work, we explore the consequences of such a discovery for baryogenesis first within a model-independent effective field theory approach. We then refine our analysis by including a source of CP violation and different hierarchies between the scales of new physics using a simplified model. We analyse the implication for baryogenesis in different scenarios and confront our results with complementary experimental constraints from dinucleon decay, LHC, and meson oscillations. We find that for a small mass hierarchy between the new degrees of freedom, an observable rate for n- n ¯ $$ \overline{n} $$ oscillation would imply that the washout processes are too strong to generate any sizeable baryon asymmetry, even if the CP violation is maximal. On the other hand, for a large hierarchy between the new degrees of freedom, our analysis shows that successful baryogenesis can occur over a large part of the parameter space, opening the window to be probed by current and future colliders and upcoming n- n ¯ $$ \overline{n} $$ oscillation searches.